2002
DOI: 10.1097/00000542-200202000-00021
|View full text |Cite
|
Sign up to set email alerts
|

Older Age Is the Strongest Predictor of Postoperative Atrial Fibrillation

Abstract: Advanced age and preoperative heart rate identify patients at high risk for development of AF after thoracic surgery. Postoperative AF occurs more frequently in patients with greater postoperative morbidity and length of hospitalization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

17
102
5

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(124 citation statements)
references
References 21 publications
(38 reference statements)
17
102
5
Order By: Relevance
“…The association between AF and advanced age in the general population is well documented, 12 as it is the greatest incidence of AF in elderly patients in the early postoperative period after CABG. 13 Our study has confirmed the above findings during the postoperative period, but it is the first to show that beyond the 6-week postoperative period the incidence of AF is unrelated to age. Information available in this study is not enough to explain this finding.…”
Section: Discussionsupporting
confidence: 86%
“…The association between AF and advanced age in the general population is well documented, 12 as it is the greatest incidence of AF in elderly patients in the early postoperative period after CABG. 13 Our study has confirmed the above findings during the postoperative period, but it is the first to show that beyond the 6-week postoperative period the incidence of AF is unrelated to age. Information available in this study is not enough to explain this finding.…”
Section: Discussionsupporting
confidence: 86%
“…[26] Increased sympathetic activation and prolonged atrial conduction time by aging are likely responsible for PoAF development. [27] Amar et al [28] reported that in patients older than 60 years POAF was more common and Hosokawa et al [29] reported that for every additional 10-year increment in age, there was an associated 1.5 times increased risk for the development of POAF.…”
Section: Discussionmentioning
confidence: 99%
“…22 The incidence of AF increases with age (34 yrs); indeed the strongest risk for postoperative AF is age >60 years. 23 Postoperative AF extends hospital stay with accompanying increased costs as well as a greater risk of stroke. 22,24 A better understanding of the mechanisms responsible for postoperative AF has led to the study of statins in this setting.…”
Section: Discussionmentioning
confidence: 99%